Integrating PjBL-STEAM with Balinese Meru Architecture to Enhance Students' Mathematical Conceptual Understanding - Putri, Putu Eka Widyantini; Astawa, I Wayan Puja; Suharta, I Gusti Putu (International Journal of Education, Management, and Technology, 2025)
Traditional mathematics education often struggles to connect abstract concepts with real-world relevance, particularly in geometry, where students find it challenging to visualize spatial relationships and applications. This study addresses this gap by integrating Balinese Meru temple architecture into a Project-Based Learning (PjBL) model infused with STEAM (Science, Technology, Engineering, Arts, Mathematics) to improve students’ conceptual understanding of geometry. A quasi-experimental post-test-only control group design was employed, involving 63 eighth-grade students (31 in the experimental group and 32 in the control group) at SMP Negeri 1 Singaraja, Indonesia. The experimental group participated in PjBL-STEAM activities exploring Meru temple geometry, while the control group received conventional instruction. Data were collected through post-tests assessing conceptual understanding, analyzed using independent sample t-tests, and supplemented with observations and interviews. Results indicated that the PjBL-STEAM approach incorporating Meru temple geometry significantly outperformed conventional methods, with the experimental group achieving a higher mean score (81.84 vs. 73.05, p = 0.024). Students demonstrated an improved ability to articulate geometric concepts, identify relevant examples, and apply their knowledge within cultural contexts. The study concludes that culturally contextualized PjBL-STEAM enhances conceptual mastery by bridging abstract mathematics with tangible cultural artifacts, suggesting its potential for broader application in other educational areas.